Analisis Prediksi Kebangkrutan Pada Perusahaan Sub Sektor Kontruksi dan Bangunan Yang Terdaftar Di Bei - Risma, Juwita; Munandar, Aris (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to analyze and predict bankruptcy in construction and building sub-sector companies listed on the IDX. This type of research is descriptive using quantitative data types. The research instrument uses a list of tables consisting of working capital data, total assets, current assets, current liabilities, total debt, net profit before tax expense and net profit of construction and building sub-sector companies listed on the IDX from 2017 to 2021. The population used in this study is all company reports in the construction and building sub-sector that are listed on the IDX from 2017 to 2021 in the form of balance sheets and profit and loss reports. The sample in this study is the financial statements of the balance sheets and profit and loss of construction and building sub-sector companies registered on the IDX for 5 years, from 2017 to 2021. The sampling technique used in this study was a purposive sampling technique. Data collection techniques using documentation and literature study. The data analysis technique used was the 1984 Modified Altman Z-Score Model, descriptive analysis and one sample t-test. The results showed that the altman z-score for the construction and building subsector companies listed on the IDX was less than 2.6, which means that the construction and building subsector companies listed on the IDX were in the gray zone to the distress zone.